Building a Physical Test Battery for Selecting Soccer Goalkeepers for Ages (10 – 12) Years - Ali, Hussein (Journal of Physical Education, 2015)
The research aims to: Building a Physical Test Battery For Selecting Soccer Goalkeepers For Ages (10 – 12) years. The researcher used the descriptive survey manner to reach a solution to the problem of research.Research community comprised of (66) soccer goalkeepers for age (10-12 years) and they were as follows (10) goalkeepers to the experiment exploratory and (56) goalkeepers to the building. In order to obtain data and information on the subject of research, researcher used the following means: Observation, scientific references, interviews with experts and specialists, questionnaires and tests & measurement. To find a solution to the problem of research, researcher used statistical means the following: The relative importance, percentage Percent, mean, standard deviation, median, coefficient of skewness, simple correlation coefficient (Pearson), T-Test for correlated samples (independent), factor analysis, The data were statistically treated using the statistical pack (SPSS).From the results it has been reached the researcher found: Firstly: factor analysis using orthogonal rotation, which was conducted on 12 variables representing special tests of physical capacity for soccer goalkeepers and that showed (4) variables were accepted (3) of them in the light of the conditions for the acceptance factors and factors were accepted are:1 - Reaction (First factor) -2 – Flexibility (second factor) 3 - Explosive power of the arms (third factor). Secondly: the Physical abilities Test Battery was extracted for soccer goalkeepers for ages (10-12) years in order of its parameters learned which represent the highest saturation on their factors units, and as following: 1 - Nelson Test in two Directions for reaction.2 - Bend the trunk forward / down from the sitting position Test. 3 - Throwing a Medical ball weighing 1 kg Test, in one hand from standing to far away as possible. The recommendations are: 1- Adoption test battery obtained and use the tests to benefit from them in the selection of soccer goalkeepers for (10-12) years.2- Make a similar studies in aspects that were not in this study like skills, psychological, functional and physical measurements